2014
DOI: 10.1007/s00405-014-3195-z
|View full text |Cite
|
Sign up to set email alerts
|

Orbital complications in children: differential diagnosis of a challenging disease

Abstract: Orbital swelling in children presents diagnostic and therapeutic challenges. Most are associated with acute sinusitis with complicating factors possibly including: amaurosis, meningitis, intracranial abscess or even cavernous sinus thrombosis. However not all acute orbital swelling is associated with acute sinusitis. A careful evaluation is critical prior to initiating therapy. Clinical records of 49 children (27 girls, 22 boys, with an average age of 11.8 years) were retrospectively reviewed. Historical data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 34 publications
1
14
0
4
Order By: Relevance
“…Laboratory tests, including assessment of white blood cell counts and serum C-reactive protein levels may be useful, as inflammatory markers are generally higher in children with SROIs than in those with peri-orbital cellulitis unrelated to complicated rhinosinusitis; it has also been reported that the presence of fever, a white blood cell count of >11,100 per microlitre, and proptosis are independent predictors of SPA or OA [31].…”
Section: Diagnosismentioning
confidence: 99%
“…Laboratory tests, including assessment of white blood cell counts and serum C-reactive protein levels may be useful, as inflammatory markers are generally higher in children with SROIs than in those with peri-orbital cellulitis unrelated to complicated rhinosinusitis; it has also been reported that the presence of fever, a white blood cell count of >11,100 per microlitre, and proptosis are independent predictors of SPA or OA [31].…”
Section: Diagnosismentioning
confidence: 99%
“…Differential diagnosis Inflammation of the tissues around the eye is a common feature of various conditions (Welkoborsky et al 2015). Orbital cellulitis, in which orbital inflammation is a sign, is uncommon but can be life threatening.…”
Section: History and Examinationmentioning
confidence: 99%
“…[8] It can be a long-term complication of midfacial or paranasal sinus infections and has high mortality and morbidity rates. Staphylococcus aureus is the responsible pathogen in 70% of cases, while Streptoccocus pneumoniae, gramnegative bacilli, anaerobes, and fungi such as Aspergillus sp.…”
Section: Discussionmentioning
confidence: 99%